Penerapan manajemen risiko sebagai pilar utama pertumbuhan dan stabilitas industri perbankan syariah - Rachmadaniyah, Shafa Ardhia (Maliki Interdisciplinary Journal, 2024)
Risk management strategies are very necessary for all companies, especially Islamic banks. Banks must implement risk management because it is very important, namely the processes and methodologies used to identify, measure, monitor, and stop risks that arise from all their business activities. The precautionary principle must be applied during the Islamic banking risk management process to identify, search, manage, and measure risks, so that Islamic banks can expand their markets quickly. To carry out sharia banking operations, sharia principles must be applied, so a strong regulatory framework is needed to create an environment that supports the growth and development of sharia banking as well as the stability of the financial industry as a whole. Risk management in Islamic banks needs special attention to be more effective. This research uses data reviewed from relevant literature about the problem discussed. The results of this research show that the common risks in Islamic banking consist of financing risk, benchmark risk, liquidity risk, operational risk, and market risk.